Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Is there a formula like $$ EX=\sum_{i=1}^{\infty}P\left(X\geq i\right) $$

(which can be found on Wikipedia and holds for positive $X$) for $EX^{n}$ ?

And I don't mean this one,

$$ EX^{n}=\sum_{i=1}^{\infty}P\left(X\geq\sqrt[n]{i}\right), $$

which is immediate, if we take $Y=X^{n}$ and use the above formula for $Y$. I mean a "more elegant" one - if there is one.

share|improve this question

1 Answer 1

up vote 6 down vote accepted

One has $$ \mathrm E(X^n)=\sum_{i=1}^\infty(i^n-(i-1)^n)\,\mathrm P(X\geqslant i). $$ More generally, $$ \color{red}{\mathrm E(u(X))=u(0)+\sum_{i=1}^\infty(u(i)-u(i-1))\,\mathrm P(X\geqslant i)}. $$ To prove this, call $(\ast)$ the RHS and note that $\mathrm P(X\geqslant i)=\sum\limits_{k=i}^\infty\mathrm P(X=k)$, hence $$ (\ast)=u(0)+\sum_{i=1}^\infty(u(i)-u(i-1))\,\sum_{k=i}^\infty\mathrm P(X=k), $$ that is, $$ (\ast) = u(0)+\sum_{k=1}^\infty\mathrm P(X=k)\sum_{i=1}^ku(i)-u(i-1) =u(0)+\sum_{k=1}^\infty\mathrm P(X=k)(u(k)-u(0)), $$ and, finally, $$ (\ast) = u(0)\mathrm P(X=0)+\sum_{k=1}^\infty\mathrm P(X=k)u(k)=\mathrm E(u(X)). $$

share|improve this answer
    
The same way you get the original, write $P(X \ge i) = \sum_{k=i}^\infty P(X=k)$ and interchange the sums. –  Nate Eldredge May 9 '12 at 15:36
    
Could you give me an explanation or at least a hint, how one arrives at this formula ? –  user26698 May 9 '12 at 15:39
    
ah, ok, thanks. –  user26698 May 9 '12 at 15:40
    
You are welcome. –  Did May 9 '12 at 15:43

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.